Pengaruh Korupsi, Tingkat Pengangguran Terbuka Dan Bonus Demografi Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 2004-2023 - Gea Anisa Kusuma Ananda; Dimas Pratomo; Mia Selvina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Economic growth is the process of increasing the economic welfare of a country within a certain period of time. Therefore, economic growth is important in assessing the success of a country in achieving its economic development. This study aims to analyze the effect of corruption, open unemployment rate and demographic bonus on economic growth in Indonesia in the short and long term. This research uses a quantitative type with a Vector Error Correction Model model. The type of data collected is secondary data sourced from the Transparency International website and the Central Bureau of Statistics. The results of the discussion of this study indicate that in the short term corruption and demographic bonus affect economic growth while the open unemployment rate has no effect on economic growth. In the long run corruption, open unemployment rate and demographic bonus affect economic growth